A prototype for communitising technology: development of a smart salt water desalination device - F. M., Fakharuddin; Fatchurrohman, Nanang; S., Puteh; H. M. A. R., Puteri (IOP Publishing, 2018)
Desalination is defined as the process that removes minerals from saline water or commonly known as salt water. Seawater desalination is becoming an attractive source of drinking water in coastal states as the costs for desalination declines. The purpose of this study is to develop a small scale desalination device and able to do an analysis of the process flow by using suitable sensors. Thermal technology was used to aid the desalination process. A graphical user interface (GUI) for the interface was made to enable the real time data analysis of the desalination device. ArduinoTM microcontroller was used in this device in order to develop an automatic device.